Some Fundamentals in the Theory of Velocity - Ellis, Howard S. (Quarterly Journal of Economics, 1938)
Introduction: contra-quantity-theory causation with Keynes, 431. — I. Working balances and the “overlapping” of payments: description, importance, illustrative cases, effects on circuit velocity or monetary requirements, 433. — II. Working balances and differentiation: behavior of circuit and transactions velocity, 446. — III. Real balances in the active circulation: relations of circuit and transactions velocity with real balances, 450. — IV. Idle balances or hoards: the Keynes-Robertson debate on losses and hoarding, the basic character of hoards, 457. — V. Division of money stock into working and idle balances, its connection with causation, Harrod's representation of Keynes, actual causation with Keynes, conclusion, 461.